The Socioecological Educator
XV, 231 p. 8 illus., 6 illus. in color.
Keywords: This volume offers an alternative vision for education and has been written for those who are passionate about teaching and learning, in schools, universities and in the community, and providing people with the values, knowledge and skills needed to face complex social and environmental challenges. Working across boundaries the socio-ecological educator is a visionary who strives to build community connections and strengthen relationships with the natural world. The ideas and real-world case studies presented in this book will bring that vision a step closer to reality.